Pharmacogenomics in chronic pain therapy: From disease to treatment and challenges for clinical practice - Yamamoto, Priscila Akemi [UNESP]; Conchon Costa, Ana Carolina; Lauretti, Gabriela Rocha; De Moraes, Natália Valadares [UNESP] (Taylor & Francis, 2019)
Pharmacogenomics (PGx) has emerged as an encouraging tool in chronic pain therapy. Genetic variations associated with drug effectiveness or adverse reactions (amitriptyline/nortriptyline/codeine/oxycodone/tramadol-CYP2D6, amitriptyline-CYP2C19, carbamazepine-HLA-A, carbamazepine/oxcarbazepine-HLA-B) can be used to guide chronic pain management. Despite this evidence, many obstacles still need to be overcome for the effective clinical implementation of PGx. To translate the pharmacogenetic testing into actionable clinical decisions, the Clinical Pharmacogenetics Implementation Consortium has been developing guidelines for several drug-gene pairs. This review will show the applicability of PGx in chronic pain from disease to treatment; report the drug-gene pairs with strongest evidences in the clinic; and the challenges for the clinical implementation of PGx.
Keywords: anticonvulsants; chronic pain; CPIC; cytochrome P450; opioids; pharmacogenetics; tricyclic antidepressants